Implementasi Transmisi Sinyal TV pada Media Transmisi Fiber Optik Singlemode - Nadhia Syafira Arifianti; Yoyok Heru Prasetyo Isnomo; Koesmarijanto Koesmarijanto (Jurnal Jaringan Telekomunikasi, 2020)
The results of TV service output using the Hybrid Fiber Coaxial system obtained a signal quality of 74% with a total of 49 channels. The attenuation with input 1 parabolic antenna receiver decoder using 200 cm fiber optic obtained a loss of 1.79 dB and at length of 2 km the loss is 8.91 dB. Whereas with the input of 2 decoder, a parabolic antenna receiver using 200 cm fiber optic, the value of losses is 1.93 dB and at 2 km the loss is 9.83 dB. The average deviation of RGB errors in the largest television image output results is Green by 0.226% and the lowest error deviation is Red at 0.148%. The effect of audio and video output before adding fiber optic devices is obtained, the audio output voltage value is 1.792 V and the video output voltage value is 2.591 V. After adding the fiber optic device the value of the output voltage with 1 television output and 1 decoder receiver at a length of 200 cm audio is 1.144 V and video is 1.167 V while at a length of 2 km the audio is 0.834 V and the video is 1.005 V.